Peningkatan Produktifitas Teaching Factory Industrial Robotic and Automation sebagai Pusat Inovasi Peralatan Laboratorium Pendidikan Vokasi - Risfendra, Risfendra; Sukardi, Sukardi; Sardi, Juli; Habibullah, Habibullah; Hendra, Ayu; Setyawan, Herlin (Jurnal Pendidikan Teknik Elektro, 2025)
The Teaching Factory Industrial Robotics and Automation ( TEFA IRA) at Universitas Negeri Padang (UNP) represents an innovative vocational education model integrating practice-based learning with real-world production activities. As an innovation hub, TEFA IRA produces laboratory equipment to support vocational learning, trains vocational high school (SMK) teachers, and enhances student competencies to meet the workforce's demands in the Fourth Industrial Revolution era. This study evaluates the productivity of TEFA IRA by analysing operational processes, the impact of teacher training, student learning experiences, product relevance, and collaboration with industry partners. The research employs a mixed-methods approach, combining qualitative and quantitative techniques with data collected through observation, interviews, surveys, and document analysis. The results indicate that TEFA IRA successfully produced 25 units of laboratory equipment with a 92% success rate. Training for SMK teachers improved their technology mastery scores from 3.2 to 4.1 (on a 5-point scale), while 90% of students reported that their learning experiences were relevant to workforce demands. Collaboration with industry partners reached an active involvement rate of 87%, including contributions to technology and technical training. However, TEFA IRA faces challenges, such as limited specialised expertise, the need for updated training modules, and the optimisation of facilities. Support from Universitas Negeri Padang is essential to address these challenges through strategic policies, facility enhancements, and strengthened industry partnerships. Overall, TEFA IRA has successfully established itself as an innovative and relevant Teaching Factory model for vocational education in Indonesia. This program holds significant potential to be further developed as a pioneer in technology-driven vocational education with global competitiveness.